Інтелектуально-моральна духовність в технотронному суспільстві - Міщенко, Віктор Іванович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Дисертація на здобуття наукового ступеня доктора філософії (PhD) за спеціальністю 033 – філософія. – Національний технічний університет «Харківський політехнічний інститут», Харків, 2023. Метою дисертаційної роботи є визначення концепту нового типу духовності як стратегії виживання людства на стадії переходу до планетарно-космічної цвілізації. Об’єкт дослідження: духовність як феномен культури. Предмет дослідження: інтелектуально-моральна духовність в процесі трансформації технотронного суспільства. У вступі обґрунтовано формування інтелектуально-моральної духовності, представлено зв’язок роботи з науковими програмами, планами і темами, наведено наукову новизну, представлено практичне значення отриманих результатів, надано інформацію щодо особистого внеску здобувача, представлено перелік публікацій за темою дисертації. У першому розділі дисертації «Історичний вимір духовності в контексті цивілізаційного розвитку людства» проаналізовано етапи духовного розвитку людства в історичному контексті, починаючи з давнього світу. Досліджено становлення духовності як інтелектуально-моральної в історії філософії й культурі античності, середньовіччя, Нового часу. Доведено, що в античній культурі та в середньовічної філософії відбулося становлення та формування духовності як інтелектуально-моральної. У другому розділі «Концептуальні основи інтелектуально-моральної духовності» виявлено теоретичні засади інтелектуально-моральної духовності з використанням міждисциплінарної методології. Проаналізовано засади критичного раціоналізму в інтелектуально-моральній духовності, доведено, що раціоналізм є досягненням людської цивілізації, концептуальною основою перетворення світу, основою формування культури і смисловим вираженням духовності як інтелектуально-моральної. Виведено соціальні засади науки в контексті постпозитивізму на тлі розвитку духовних процесів. Виділено культурологічні аспекти інтелектуально-моральної духовності, проаналізовано поняття духовності в контексті культури. Виявлено взаємозв'язок духовності і культури, показано вплив культури на інтелектуальне і моральне вдосконалення особистості. Проаналізовано духовно-інтелектуальні аспекти філософії космізму. В третьому розділі «Інтелектуально-моральна духовність як стратегія виживання та розвитку технотронного суспільства» розглянуто інтелектуально-моральну духовність як духовність перехідного періоду людства до планетарно-космічної цивілізації. Зроблено висновок про те, що у процесі еволюційного розвитку соціуму виникає складна суперечлива структура: антропо-інфо-техно-екосфера. Через складність та нерівномірність розвитку вона ініціює певні «девіаційні хвилі», що негативно впливають на духовний світ людини та стан екосистеми. Виходячи з необхідності гармонізації цієї структури, запропоновано стратегію розвитку технотронного суспільства та розроблена концепція інтелектуально-моральної духовності. У четвертому розділі «Духовний образ особистості: антропологічні виміри інтелектуально-моральної духовності» інтелектуально-моральна духовність розглянута вв аспекті духовного розвтку людини. Розроблена комплексна модель духовного образу особистості, яка складається з трьох компонентів: відкритості світу, інтелектуальності та здатності до творення. Розглянуто чотири етапи духовного розвитку особистості, які вона проходить протягом життя від усвідомлення власного існування як людини до найвищих етапів духовної зрілості. Виділено чотири форми девіації духовності особистості – бездуховність, гіпертрофована форма духовності, антидуховність, квазідуховність та можливість духовної ентропії – руйнування духовності особистості. У висновках наведено основні результати наукової роботи щодо вирішення поставлених наукових задач дослідження. Наукова новизна отриманих результатів. У результаті виконання дисертаційної роботи набув подальший розвиток науковий напрям, пов'язаний з осмисленням ролі духовності у цивілізаційному розвитку, формуванням духовної особистості. Вперше: розглянуто умови формування інтелектуально-моральної духовності, показано її зв’язок з духовними вимірами, які існували в історичному розвитку людства. Визначено її концептуальні основи на підставі узагальнення та систематизації ідей різних філософських напрямків та визначено теоретичні, методологічні й аксіологічні засади; Запропоновано: цивілізаційний підхід з еко-антропологічним виміром, який дозволив сформувати модель розвитку духовності в процесі її історичного становлення, виявлено її онтологічний статус як основи існування та виживання людства, що дозволило вийти на проблему взаємодії природа-розум в еволюційно-історичному та культурному становленні людства Удосконалено: концепцію розвитку технотронного суспільства на основі пріорите-тного розвитку техносфери для вирішення екологічних проблем та всебічної гармонізації антропо-інфо-техно-екосфери: подальшої трансформації інформаційної сфери в інформаційно-аналітичну, безперервного інтелектуального саморозвитку людства та терраформації планети; Виявлено: онтологічний зміст інтелекту в створенні імітаційної моделі управління середовищем існування, яка передбачає можливості активної співпраці людського інтелекту з мислячим штучним інтелектом в імітаційних інтелектуальних системах аналізу біосферних процесів та формування мораль-них основ глобального колективного управління; Запропоновано та досліджено: основні етапи духовного розвитку особистості, смислові конотації структурних елементів «духовного образу» як форми прояву інтелектуально-моральної духовності в антропологічному вимірі, запропоновано теоретичні підходи формування духовного образу в контексті вищої освіти в умовах антропологічної кризи; Дістали подальшого розвитку: концепція формування глобальної загальнопланетарної моралі та духовного виховання особистості.

The thesis is submitted to obtain a scientific degree of Doctor of Philosophy, Specialty 033 – Philosophy – the National Technical University «Kharkiv Polytechnic Institute», Kharkiv, 2021. The purpose of the dissertation is to define the concept of a new type of spirituality as a strategy for the survival of humanity at the stage of transition to planetary-cosmic civilization.of the dissertation is to define the concept of a new type of spirituality as a strategy for humanity's survival at the stage of transition to planetary-cosmic civilization. Object of research: spirituality as a cultural phenomenon. The subject of research: intellectual and moral spirituality in the process of transformation of the technotronic society. In the introduction, the formation of intellectual and moral spirituality is substantiated, the connection of work with scientific programs, plans and topics is presented, scientific novelty is given, the practical significance of the obtained results is presented, information is provided about the personal contribution of the winner, a list of publications on the topic of the dissertation is presented. The first chapter of the dissertation "Historical dimension of spirituality in the context of the civilizational development of mankind" analyzes the stages of the spiritual development of mankind in the historical context, starting from the ancient world. The development of spirituality as intellectual and moral in the history of philosophy and culture of antiquity, the Middle Ages, and the New Age is studied. It has been proven that in ancient culture and in medieval philosophy, the formation and formation of spirituality as intellectual and moral took place. In the second chapter "Conceptual foundations of intellectual and moral spirituality" the theoretical foundations of intellectual and moral spirituality using an interdisciplinary methodology are revealed. The principles of critical rationalism in intellectual-moral spirituality are analyzed, it is proved that rationalism is an achievement of human civilization, the conceptual basis of the transformation of the world, the basis of the formation of culture and the meaningful expression of spirituality as intellectual-moral. The social foundations of science in the context of postpositivism against the background of the development of spiritual processes are derived. Culturological aspects of intellectual and moral spirituality are highlighted, the concept of spirituality in the context of culture is analyzed. The relationship between spirituality and culture is revealed, the influence of culture on the intellectual and moral improvement of the individual is shown. The spiritual and intellectual aspects of the philosophy of cosmos are analyzed. The third section "Intellectual and moral spirituality as a strategy for the survival and development of technotronic society" considers intellectual and moral spirituality as the spirituality of the transition period of mankind to planetary-cosmic civilization. It is concluded that in the process of evolutionary development of society there is a complex contradictory structure: anthropo-eco-techno-infosphere. Due to its complexity and uneven development, it initiates certain "deviation waves" that negatively affect the spiritual world of man and the state of the ecosystem. Based on the need to harmonize this structure, a strategy for the development of a technotronic society is proposed and the concept of intellectual and moral spirituality is developed, which includes the most significant goals and high ideals of people in their cosmic purpose. In the fourth section "The spiritual image of the individual: anthropological dimensions of intellectual and moral spirituality" intellectual and moral spirituality is considered in its anthropological dimension. A comprehensive model of the spiritual image of the individual has been developed, which consists of three components: openness to the world, intelligence and the ability to create. Consider the four stages of spiritual development of the individual, which he goes through life from the realization of his own existence as a person to the highest stages of spiritual maturity. There are four forms of deviations of the spirituality of the individual - spirituality, hypertrophied form of spirituality, anti-spirituality, quasi-spirituality and the possibility of spiritual entropy - the destruction of the spirituality of the individual. In the conclusions, the main results of the scientific work regarding the solution of the set scientific problems of the research are given. Scientific novelty of the obtained results. As a result of the dissertation work, the scientific direction related to the understanding of the role of spirituality in civilizational development and the formation of a spiritual personality gained further development. For the first time: the conditions for the formation of intellectual and moral spirituality are considered, its connection with the spiritual dimensions that existed in the historical development of mankind is shown. Its conceptual foundations are determined based on the generalization and systematization of ideas of various philosophical directions, and the theoretical, methodological, and axiological foundations are determined; It is proposed: a civilizational approach with an eco-anthropological dimension, which made it possible to form a model of the development of spirituality in the process of its historical formation, revealed its ontological status as the basis of the existence and survival of humanity, which allowed to solve the problem of interaction between nature and mind in an evolutionary - historical and cultural development of mankind. Improved: the concept of the development of technotronic society based on the priority development of the technosphere to solve environmental problems and the comprehensive harmonization of the anthropo-info-techno-ecosphere: the further transformation of the information sphere into the information-analytical, continuous intellectual self-development of humanity and the terraforming of the planet; Revealed: the ontological content of intelligence in the creation of a simulation model of management of the living environment, which provides for the possibility of active cooperation of the human intellect with thinking artificial intelligence in simulation intellectual systems for the analysis of biosphere processes and the formation of the moral foundations of global collective management; Proposed and researched: the main stages of the spiritual development of the individual, the semantic connotations of the structural elements of the "spiritual image" as a form of manifestation of intellectual-moral spirituality in the anthropological dimension, the theoretical approaches of the formation of the spiritual image in the context of higher education in the conditions of an anthropological crisis are proposed; They received further development: the concept of the formation of global all-planetary morality and spiritual education of the individual.
Intellectual and Moral Spirituality in a Technotronic Society
Keywords: дисертація; духовність; цивілізація; техніка; інформаційне суспільство; віртуальність; інтелект; концепція сталого розвитку; культура; мораль; освіта; цінності; свобода; spirituality; civilization; technology; information society; virtuality; intelligence; concept of sustainable development; culture; morality; education; values; freedom; 130.2:355.1